Factors Related To Patient Satisfaction With Hospital Health Care - Safanny Putri; Triayu Nur Afifah; Haikal Ghiffary; Aghniya Choirunnisa (STIKes Ibnu Sina Ajibarang, 2023)
Hospital health services must adapt and develop to achieve higher standards in facing competition in the health industry by improving quality and patient satisfaction. Patient satisfaction will affect the patient's desire to return to using the same hospital health care. Good service quality will also encourage patients to have confidence in using health services. The purpose of this study was to determine the factors associated with patient satisfaction with hospital health services. This research method uses a systematic review method which is sourced from several online sites such as Google Scholar and journal databases, such as PubMed. Patient satisfaction and hospital health services have a relationship because in a hospital health services patient satisfaction is generally used to assess the quality of service delivery. Based on the results of the study it can be concluded that the level of patient satisfaction can be seen from the quality of hospital health services. The quality of health services greatly affects the level of patient satisfaction in making repeat visits. To provide satisfaction and retain customers, the provision of medical services turns out to be more important based on several satisfaction factors with five dimensions such as Reliability, Assurance, Tangible, Empathy, and Responsiveness.